Mixed reality for industrial applications: interactions in human-machine system and modelling in immersive virtual environment. (17th May 2019) - Bruzzone, Agostino G.; Fancello, Gianfranco; Daga, Mariangela; Leban, Bruno; Massei, Marina
The authors propose an innovative mixed reality solution representing an immersive intuitive and interoperable environment to support service in industrial plants. These methodologies are related to concepts of Industry 4.0. Proposed solutions are based on a mix of virtual and augmented reality. Indeed the authors propose an overview of this approach and other synergistic techniques. Moreover, alternative instruments are presented and their specific advantages and disadvantages are described. Particularly, the paper proposes an innovative approach based on the SPIDER, an advanced interoperable interactive CAVE developed by the authors which supports cooperative work of several users involved in training, troubleshooting and supervision. Also, the use of such technology and approach in other fields is presented, such as the validation of training equipment for bus driving and related motion platform integrated in the SPIDER; in this case the solution is running a simulator, named 'BBBuS', used for training and RsD activities.